Characterization of methacrylated alginate and acrylic monomers as versatile SAPs. (15th July 2017) - Mignon, Arn; Vermeulen, Jolien; Graulus, Geert-Jan; Martins, José; Dubruel, Peter; De Belie, Nele; Van Vlierberghe, Sandra
Highlights: Methacrylated alginate successfully combined with acrylic acid and acrylamide. High cross-linking efficiency, measured both qualitatively and quantitatively. Limited hydrolysis in aqueous and cement filtrate solutions. Extreme swelling capacities up to 630 gwater /gSAP . Abstract: Superabsorbent polymers (SAPs) based on polysaccharides, especially alginate, could offer a valuable solution in a plethora of applications going from drug delivery to self-healing concrete. This has already been proven with both calcium alginate and methacrylated alginate combined with acrylic acid. In this manuscript, the effect of varying the degree of methacrylation and use of a combination of acrylic acid and acrylamide is investigated to explore the effects on the relevant SAP characteristics. The materials showed high gel fractions and a strong swelling capacity up to 630 gwater /gSAP, especially for superabsorbent polymers with a low degree of substitution. The SAPs also showed only a limited hydrolysis in aqueous and cement filtrate solutions.